Position signal detector for linear variable differential transformer - Rerkratn, Apinai; Luangpol, Amata; Petchmaneelumka, Wandee; Riewruja, Vanchai (My University, 2020)
This paper presents the position signal detector for linear variable differential transformer (LVDT) based on RMS-to-DC converter. The proposed detector consists of the differential amplifier, the comparator, the phase detector, the controllable unity-gain inverting/non-inverting amplifier and the RMS-to-DC converter. The proposed technique provides a simple scheme and uses the low cost commercial available devices such as opamp, transistor and digital logic gate. The experimental testing with the commercial LVDT model OP12.5G from Solartron Metrology showing the proposed position signal detector can produce the output voltage corresponding to the measured displacement with satisfactory values and good linearity.
Keywords: Displacement measurement; LVDT; Position sensor; RMS to DC converter; Signal demodulator